A newly developed layered model to analytically predict the piezoelectric property of polymeric foams: Cellular geometry consideration. Issue 17 (8th December 2021) - Daryadel, Mahsa; Azdast, Taher
Abstract: Piezoelectric property refers to the ability of materials to convert mechanical energy into electrical energy and vice versa. The development of science and technology and their orientation towards digital life will increase the need to use this property more and more. Polymeric foams are one of the materials that show high piezoelectric property. So far, only layered model has been proposed to predict the piezoelectric property of these materials. But to the best knowledge of the authors, there is no comprehensive research to investigate the accuracy of this model. Therefore, in this study, the obtained theoretical results from the layered model are compared to the experimental results and the accuracy of this model is investigated. Also, the presented solution by other authors to improve the accuracy of this model is studied. Finally, a new approach is developed to predict piezoelectric property of polymeric foams. The results show that the presented approach in this study increases the accuracy of the layered model compared to previous approaches. Considering the cellular structure of the polymeric foam as hexagonal geometry, the error is obtained 0.2%. Furthermore, the effect of different structural parameters on the maximum remnant charge density is investigated. Abstract :